Management of industrial safety and occupational health: reduction of occupational risk - Zambrano Falcón, Joel Diógenes (2022)
The control of occupational risks is a common need in all organizations due to the possibility of negative consequences on the health of professionals and employees, members of an organization oriented to carry out metal-mechanical manufacturing operations, a condition required mainly in companies that start work in the framework Peruvian legal. The purpose of the article was to analyze the management carried out in industrial safety and occupational health in reducing occupational risks expressed in incidents and accidents in a productive area dedicated to metalworking operations. To this end, the procedures of a pre-experimental study were followed with 16 observations on the operating records in a company in the metalworking sector of the Puente Piedra district, Peru, collected in 2016. It was concluded with the finding of significant evidence of differences between means of the comparison groups regarding incidents and accidents in the pre and post test evaluation.